Young men’s health and educational practices in the perspective of health promotion (Research, Society and Development, 2020)
Objectives: to describe the current relationship of young men with their health, to discuss educational practices with a view to promotion and prevention of health problems in the young male population. Method: descriptive and exploratory study, with qualitative approach, developed with 30 young university students between 18-29 years, in a public university in Rio de Janeiro, having as instrument of data collection the semi-structured interview. For data analysis, the content analysis technique was used. Results: the lack of knowledge about oneself is directly linked to the perception of care not being attributed to the male population. Health education becomes the main bridge for men to enter the primary care service, preventing this from occurring only when the disease has already set in. Conclusion: There are, still, gaps that should be better explored, because they involve the health of young men, from the perspective of gender, portraying the challenge of thinking about health as a space for the promotion and prevention of health problems, but, for this, it is essential a welcome in its entirety. The lack of visibility of this population has consequences that reflect the increase in morbidity and mortality of the young male population.